Re-Reading Hanslick's Aesthetics Die Rezeption Eduard Hanslicks im englischen Sprachraum und ihre diskursiven Grundlagen - Wilfing, Alexander (Hollitzer, 2019)
This study examines the reception of Eduard Hanslick in Anglo-american discourse from its earliest instances in the 19th century up to analytical philosophy of music. This book thus analyzes primarily the discoursive conditions of Hanslick's reception, which developed distinctly as part of different academic disciplines (history of art, musicology, philosophy of music). Moreover, this study explores the function Hanslick's argument attained in modern debates of New Musicology and Anglo-american aesthetics, which cast new light upon the interpretation of Hanslick's stances on the relation between emotion and music.